Pengaruh Harga, Kualitas Pelayanan dan Suasana Cafe Terhadap Kepuasan Konsumen (Studi pada konsumen Cafe Apung Rowo Kalmpok) - Revin Dea Lorensa; N. Rachma; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study examines the effect of price, service quality and cafe atmosphere on consumer satisfaction at the Floating Cafe Rowo Klampok in Senggreng Village, Krajan Hamlet, Sumber Pucung District, Malang Regency. The type of research used is explanatory research. The sample used in this study were 100 respondents who were consumers of the Floating Cafe Rowo Klampok. Data collection techniques using a questionnaire. The analysis technique uses multiple linear regression analysis. The results showed that price, service quality and cafe atmosphere had a significant simultaneous and partial effect on customer satisfaction. Keywords: Price, Service Quality, Cafe Atmosphere, Consumer Satisfaction